Evaluation of Results of Ilizarov Fixator and Methodology in Tibial Non- Union - Ghosh, Jayabrata; Pujari, Prashanta Kumar (Journal of College of Medical Sciences-Nepal, 2019)
Background: Treatment of non-union of tibial diaphyseal fractures has always posed a formidable challenge to surgeons. Persistant infection, deformity, bone loss, stiffness of joints and disability complicate the problem further. Ilizarov methodology tackles all the above problems simultaneously and offers a solution for non-union. Progressive new bone formation and increased vascularity following corticotomy and bone transport helps in filling bone gaps and promoting fracture union. Stability of the fixation allows early weight bearing, ambulation and joint mobilization. To evaluate the results of Ilizarov fixator in treating tibial non-union. Methods: This retrospective hospital study was conducted at Ramakrishna Mission Seva Pratishthan, Kolkata, India from August 2009 to February 2012. Forty two patients treated at this hospital between August 1994 and August 2011 with a minimum of 12 months follow up were included. The results were analysed on the outcome of bone and functional score using the Association for the Study and Applica-tion of the Method of Ilizarov (ASAMI) scoring system. Results: Of the 42 patients in this study, there were 28 (66.7%) excellent, 6 (14.3%) good, 5 (11.9%) fair and 3(7.1%) poor bone results and 17(40.5%) excellent, 20(47.6%) good, 2(4.8%) fair and 3(7.1%) poor functional results. Conclusions: Treatment of tibial non-unions with Ilizarov fixator is effective but not without considerable amount of complications and morbidity associated with it. The functional outcome was largely multifactorial and dependent on the final joint function, soft tissue condition and ability of the patient to return to activity.